SENANDUNG MENIDURKAN ANAK SEBAGAI UPAYA PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER TERHADAP ANAK - NFN Marlina (Balai Bahasa Kalimantan Barat, 2019)
This study aims to describe and analyze the values of character education contained in the lullaby of Siak Malay community in Riau. The research problem is what character education values contained in the lullaby in the Siak Malay community. To find the values of character education contained in the lullaby, the qualitative descriptive method is used, which is a method that exposes writing based on the content of the lullaby. The result of the study shows that the lullaby contains the value of faith and piety, intelligence, morality and character. From the results of this study, it can be concluded that the lullaby can be used as a tool to implement the value of character education for children.